Pengaruh biaya operasional dan kurs terhadap pendapatan pada PT. Smartfren Telecom, Tbk - Mengga, Grace Sriati; Batara, Mince; Toding, Marsita Lambe’ (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Since 2009, the business development of PT Smartfren Telecom has continued to suffer losses. Apart from the high competition, the losses experienced by PT. Smartfren Telecom, Tbk also comes from high operating expenses and also from foreign exchange losses. The purpose of this study is to determine the effect of operating costs and exchange rates on revenue at PT. Smartfren Telecom, Tbk in 2017-2020. The type of research used in this research is descriptive research with a quantitative approach. The data collection method used is a documentation technique based on the company's financial statements published by the Indonesia Stock Exchange. The type of data used in this study is secondary data which is data in the form of documents obtained from the official website of the Indonesia Stock Exchange. Analysis of the data used is multiple linear regression analysis. Hypothesis testing is done by partial test (t test) and simultaneous test (F test). For operational costs partially have a negative and significant effect on income while the exchange rate has a negative and insignificant effect on income. For simultaneous test results, operating costs and exchange rates have a significant effect on income.